Revolutionizing Mosque Financial Transparency in Indonesia: Revolusi Transparansi Keuangan Masjid di Indonesia - Berlian, Alliyah Ayu Prismawanti; Rahayu, Duwi (Indonesian Journal of Law and Economics Review, 2024)
This study aims to analyze the preparation of the financial reports of the Nurul Anwar Mosque BCF based on ISAK 35, supported by the principles of habluminallah and habluminannas, to enhance transparency and accountability. The research employs a descriptive qualitative method. Primary and secondary data were collected through interviews, observation, and documentation. The data analysis involved identifying relevant theories, collecting data, assessing its alignment with ISAK 35, reconstructing the financial statements, and drawing conclusions. The findings indicate that the financial reports of the BCF Nurul Anwar Mosque are currently simple, comprising only income and expenses. These reports were reconstructed according to ISAK 35. The principles of habluminallah and habluminannas were integrated into the preparation of these reports, as every transaction was recorded with valid evidence, ensuring accountability to both Allah and humans. This study contributes to the existing literature by providing insights into the application of ISAK 35 in religious institution financial reporting, highlighting the importance of integrating spiritual principles to achieve comprehensive accountability. Highlight: Current Simplicity: Financial reports are currently limited to income and expenses. ISAK 35 Alignment: Reconstructed financial statements now adhere to ISAK 35 standards. Enhanced Accountability: Integrating spiritual principles ensures accountability to Allah and humans. Keywoard: ISAK 35, Financial Reporting, Transparency, Accountability, Mosque Finance